2017
DOI: 10.1039/c6sc04455g
|View full text |Cite
|
Sign up to set email alerts
|

Versatile routes for synthesis of diarylamines through acceptorless dehydrogenative aromatization catalysis over supported gold–palladium bimetallic nanoparticles

Abstract: In the presence of Au–Pd/TiO2, various kinds of symmetrically and unsymmetrically substituted diarylamines could effectively be synthesized starting from various combinations of substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 77 publications
3
16
0
Order By: Relevance
“…Besides this, two primary amine reactants could generate a secondary amine and ammonia. 25,60,61 The released ammonia could, in turn, yield the primary cyclohexylamine by reductive amination with cyclohexanone. Therefore, a small excess of 1.4 equivalents of the amine reactant with respect to phenol was used in each reaction.…”
Section: Amine Reactant Scopementioning
confidence: 99%
“…Besides this, two primary amine reactants could generate a secondary amine and ammonia. 25,60,61 The released ammonia could, in turn, yield the primary cyclohexylamine by reductive amination with cyclohexanone. Therefore, a small excess of 1.4 equivalents of the amine reactant with respect to phenol was used in each reaction.…”
Section: Amine Reactant Scopementioning
confidence: 99%
“…In this sense, the sustainable transformation of lignocellulose-based substrates (e.g., aldehydes, ketones, phenols, alkenes and alkynes) into amines have been reported as a promising way to replace oil from its actual applications [6] , [7] , [8] , [9] . Among them, the heterogeneously catalyzed reductive amination of ketones has drawn great attention as a method for the synthesis of primary or higher-order amines [10 , 11] . This paper describes a protocol based on our research on Liquid phase amination of Cyclohexanone-to-Secondary amines over Carbon-supported Pd catalysts.…”
Section: *Methods Detailsmentioning
confidence: 99%
“…Moreover, they demonstrated that the variation in temperature, concentration of NH 3 , and H 2 availability were significant in controlling the reaction toward the desired product. Their results suggest that the reaction proceeds according to the general steps described by Taniguchi et al [17] . and Koizumi et al., [18] in which the product distribution is affected by the hydrogenation of the imine to form cyclohexylamine or its dehydrogenation to form aniline.…”
Section: Introductionmentioning
confidence: 91%
“…The ketone condenses with the amine to produce an imine intermediate ( 3 ), which is subsequently converted into the desired amine ( 4 ) via hydrogenation or dehydrogenation (Scheme 1). [17,18] This process usually implies the formation of side products (tertiary amines, alcohols, etc.) and thus, catalytic materials must be used to control the selectivity toward the desired product [15,19–21] …”
Section: Introductionmentioning
confidence: 99%